DEVELOPMENT OF SYMBOLS - Mohira Abdurakhmonova (Web of Journals Publishing, 2024)
This article is devoted to the reasons for the appearance of symbols and the stages of their introduction into works of art. Until now, scientific opinions about how the symbol has been formed have been analyzed, as well as the stages of development up to the artistic work have been discussed.
Keywords: symbol, convention, myth, cultural information, collective memory, color symbols, number symbols, folklore, new form.